IMPLEMENTASI CONTENT-BASED RETRIEVAL PADA PERPUSTAKAAN DIGITAL BERBASIS OPEN SOURCE MENGGUNAKAN APACHE LUCENE - David David (SISFOTENIKA, 2011)
Abstract : Applications are built can be used to classification search result documents and documents search easier. Documents that are only for the article from journal, thesis, ebook and other documents. Indexing and searching documents using Lucene as a search engine. An filing text document often needed for finding document that content special word or combination of some words. In this research, is made application that can save and retrieve text document, using java program language, db4O and Lucene Library. For efficient in saving, data stop word eliminated, and take account the existent of synonim words. In retrieving document it is possible using operator AND, OR and NOT with the number of words priority that exist in that document. The process of searching are divided into two, namely Simple Search and Advanced Search. Simple Search using a query to search Db4o while Advanced Search using the search terms in the index using Lucene library. In this system the test results obtained are accurate.Keywords : Apache Lucene, Indexing, TF-IDF